Analysis of Contact Characteristics of Carbon Brush/Slip Ring under Eccentric Oscillation of Hydrogenerator Rotor - Xinze Zhao; Yunfeng Nie; Ming Chen; Hongling Qin; Xiang Xu (Shock and Vibration)
In this paper, the contact characteristics of the carbon brush/slip ring of the hydrogenerator under the eccentric vibration of the rotor are studied. The influence of spring parameters on the contact loss of the carbon brush/slip ring was studied by establishing the motion model of the carbon brush/slip ring for theoretical calculation and fitting the motion trajectory curve with MATLAB software. Studies have shown that the loss of contact is mainly related to the spring damping coefficient and the precompression. By optimizing these two parameters, the contact stability of the carbon brush on the ring surface of the slip ring can be improved. It provides a theoretical reference for the design and optimization of the parameters of the carbon brush/slip ring spring.